Assessing the Effect of Geometric Design and Land Use on Roundabouts Using Video Camera - Al-Mistarehi, Bara; Imam, Rana; Al-Shawabkah, Majdoleen M.; Shtayat, Amir; Al-Omari, Aslam (Civil Engineering Journal, 2024)
This study is concerned with assessing the effect of geometric design and land use on roundabouts, which are one of the most widely used traffic calming techniques. It aims to study the speed profiles before, at, and after thirty selected roundabouts in Jordan to develop models for predicting the circulating speed for through movement as a function of the land use of the roundabout, the roundabout geometric characteristics, and the approaching highway free-flow speed. A laser radar gun was used to capture speed data, and geometric characteristics were extracted from video pictures. Various parameters were employed to simulate the circulating speed, including the roundabout diameters, free flow speed, entry deviation angle, approaching highway exit width, circulating roadway width, and entry width. Speed profiles were developed for six roundabout types with different land uses and geometric characteristics. It was found that the roundabout effect on speed reduction extends to 150 m downstream the exit and upstream the entry. It was also discovered that the rate of reduction varies according to the upstream street free flow speed (FFS), with dramatic decreases observed at the last 50 m upstream of the entry. Variability in the speed values around the midpoint of the circulatory roadway was observed, with speed at the exit being higher than that at the entry. Doi: 10.28991/CEJ-2024-010-11-012 Full Text: PDF